Effect of Lumbar Disc Degeneration and Low-Back Pain on the Lumbar Lordosis in Supine and Standing: A Cross-Sectional MRI Study. Issue 21 (November 2015) - Hansen, Bjarke B.; Bendix, Tom; Grindsted, Jacob; Bliddal, Henning; Christensen, Robin; Hansen, Philip; Riis, Robert G.C.; Boesen, Mikael
Abstract : Study Design: Cross-sectional study. Objective: To examine the influence of low-back pain (LBP) and lumbar disc degeneration (LDD) on the lumbar lordosis in weight-bearing positional magnetic resonance imaging (pMRI). Summary of Background Data: The lumbar lordosis increases with a change of position from supine to standing and is known as an essential contributor to dynamic changes. However, the lordosis may be affected by disc degeneration and pain. Methods: Patients with LBP >40 on a 0 to 100 mm Visual Analog Scale (VAS) both during activity and rest and a sex and age-decade matching control group without LBP were scanned in the supine and standing position in a 0.25-T open MRI unit. LDD was graded using Pfirrmann's grading-scale. Subsequently, the L2-to-S1 lumbar lordosis angle (LA) was measured. Results: Thirty-eight patients with an average VAS of 58 (±13.8) mm during rest and 75 (±5.0) mm during activities, and 38 healthy controls were included. MRI findings were common in both groups, whereas, the summation of the Pfirrmann's grades (LDD-score) was significantly higher in the patients [(MD 1.44; 95% confidence intervals (CI) 0.80 to 2.10; P < 0.001]. The patients were less lordotic than the controls in both the supine (MD −6.4°; 95% CI −11.4 to −1.3), and standing position (MD −5.6°; 95% CI −10.7 to −0.7); however, the changes between the positions (ΔLA) were the same (MD 0.8°; 95% CI −1.8 to 3.3). Using generalized linear model the LDD-score was associated with age ( P < 0.001) for both groups. The LDD-score and ΔLA were negatively associated in the control group ( P < 0.001), also after adjustments for gender and age (β-coefficient: −2.66; 95% CI −4.3 to −1.0; P = 0.002). Conclusion: Patients may be less lordotic in both the supine and standing position, whereas, change in the lordosis between the positions may be independent of pain. Decreasing lordosis change seems to be associated with age-related increasing disc degeneration in healthy individuals. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the text